Elementary School Students' Strategies for Solving Area Measurement Problems - Indah Permatasari; Mohammad Faizal Amir (Universitas PGRI Semarang, 2023)
This study aims to identify the strategies used by elementary school students in solving area measurement problems. The research method used was a descriptive qualitative approach. The data collection techniques used in this research are task, interview, observation, and documentation. The data presentation techniques used were data reduction, data presentation, and conclusion drawing/verification. The research subjects used were elementary school students in grades 3, 4, 5, and 6. In this study, it was found that there were six strategies used by students in solving area measurement problems, namely 1) counting the number of square units, 2) decomposing the shape, 3) applying length reasoning, 4) counting all units, 5) multiplying length and width, 6) dividing the whole by the number of divisions. Counting all units is the most widely used strategy by elementary school students. Solving area measurement problems is influenced by students' experience obtaining area measurement material. The results of this study suggest that students prioritize strategies in problem solving. If the strategy students use is correct, then the arrangement structure regarding the solution will be appropriate.